Creating Quality Tourism Destinations: The Crucial Role of Community Participation and Government Support in Batur UNESCO Global Geopark - Bali - I Wayan Mertha; Putu Irma Yunita; Ni Made Tirtawati (Centre of Excellence in Tourism Udayana University, 2025)
The quality of tourist destinations is determined by both supply and demand factors, highlighting the crucial role of stakeholder collaboration in achieving sustainable development. This study investigates how government initiatives and local community participation contribute to destination quality, with particular attention to community satisfaction. The research was conducted in the Batur Global Geopark, a UNESCO-recognized area that represents both natural and cultural heritage. Data were collected from 150 local community leaders through a self-administered questionnaire, and the analysis was carried out using Partial Least Squares Path Modelling (PLS-PM). The findings demonstrate that active community participation has a significant and positive impact on enhancing destination quality. Moreover, the study emphasizes that effective collaboration requires strong alignment between governmental development programs and community aspirations. Without such alignment, initiatives may face challenges in implementation and fail to address the actual needs of local stakeholders. This research provides practical implications for policymakers and destination managers. It suggests that participatory planning should be prioritized to ensure inclusiveness and long-term effectiveness. In addition, establishing continuous dialogue and communication channels between stakeholders—government, local communities, and tourism managers—is essential for fostering trust, shared responsibility, and sustainable growth. By integrating community perspectives into destination development strategies, policymakers can ensure that tourism not only attracts visitors but also enhances the welfare and satisfaction of the local population.